Museformer: Transformer with Fine- and Coarse-Grained Attention for Music Generation - Yu, Botao; Lu, Peiling; Wang, Rui; Hu, Wei; Tan, Xu; Ye, Wei; Zhang, Shikun; Qin, Tao; Liu, Tie-Yan (2022)
Abstract to come...